Pelaksanaan Pengelolaan Hama Terpadu (PHT) Padi di Desa Kluwan, Kecamatan Penawangan, Kabupaten Grobogan - M. Eti Wulanjari; Endan Iriani; Khairi Anwar (Jurnal Ilmiah ESAI, 2010)
The objective of the research is to know farmer response to Integrated Pest Management application. This research was held in Kluwan Village, Penawangan District, Grobogan Regency. This location was elected based on purposive method, since Kluwan Village was the centre of Primatani activity, and has been introduced to Integrated Pest Management (IPM). This research was designed by census in July 2007 to 14 core members of Gapoktan, The results were (1) the highest knowledge of respondent showed that (92, 86%) interested to IPM was 57, 15%, and the effort to increase rice yield with high yield variety and increase fertilizer dosage were 50%; (2) respondent attitude to IPM was researched and preferred were using seed treatment, mouse trap, compost, mechanical pest management, and weed management with herbicides. Otherwise, chemical pesticides and NPK fertilizer still preferred by a lot of respondents; (3) the main problem was compost supply difficulty and planting with young seed; (4) the urgent component are using high yield variety and compost. Key words: respond, Integrated Pest Management